Faktor-faktor yang Mempengaruhi Permintaan Tahu di Kecamatan Tampaksiring - GEDE JAYENG MAHATMA; I GUSTI AYU AGUNG LIES ANGGRENI; I KETUT RANTAU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Factors that Influence the Demand for Tofu in Tampaksiring Sub-district This study aims to determine the factors that Influence the demand for tofu in theTampaksiring District area. Location selection was done intentionally (porposive),sampling points were carried out in Pejeng Village and Tampaksiring Village. Thepopulation in this study is household consumers who buy and consume tofu and asdecision makers in buying tofu. The samples taken were 60 people with accidentalsampling technique. In this study using a multiple linear regression analysis modelusing statistical criteria namely F test, t test and R2.The results showed that the resultsof the F test were six variables, namely: price, price of tempe, price of eggs, number offamily members, last education and family income together influencing the demand fortofu in Tampaksiring District. Partially the results of the t-test analysis show that at the95% confidence level the variables that partially influence the demand for tofu inTampaksiring District are the price, the price of tempeh, the price of eggs.The results ofthe study revealed that most people consume tofu based on the nutritional benefitscontained in it. This is expected to be an opportunity for tofu entrepreneurs inTampaksiring District to increase production and supply of tofu products in order tofulfill the demand for tofu in Tampaksiring Sub-district.